MOTIVASI SWISS MELAKUKAN REFERENDUM IMIGRASI PADA TAHUN 2014 - Vemby "; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains about motivation of Switzerland for a referendum as an effort to limit immigration and keeping national’s security balance in 2014. Switzerland as the heart of Europe had agreement with European Union about Free Movement on Persons that will be the main reason of increasing immigrant and asylum seekers. Switzerland have long connection with immigrant and asylum seekers who have contribute and support for national economy. This research has been built by neo-realism perspective on International Relations and support by securitization and migration theories, and also concept of referendum. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative descriptive methods. Scope of this research is Switzerland’s immigration referendum in 2014. This research found that immigrant and asylum seekers threaten Switzerland’s security in many ways. This result shows that Switzerland fear about arising of criminality and highly social assistance that government spend for immigrant and asylum seekers. Immigration referendum is a result from people’s want to limit immigration because their negative effect, also spreading of xenophobia and islamophobia in Switzerland. The main motivation of immigration referendum is to maintain security the security of Switzerland who were disturbed by the presence of immigrant and asylum seekers.Keyword : referendum, immigration, security, securitization of migration